Pendampingan Literasi Digital dan Dakwah Media Sosial Pada LKSA Aisyiyah Kota Batu - Fahrudin Mukhlis; Zulfikar Yusuf; Ahmad Aditian Fiadha; Mohammad Soffan Wachid (Badan Penerbitan Universitas Widyagama Malang, 2023)
This program was held with the purpose to strengthen students’ literacy which sourced from digital media at the Aisyiyah for Social and Child Welfare Institution (LKSA) in Batu City. In addition, this activity is intended to provide assistance to students in using digital and social media as a medium of da'wah. This is in line with the mission of the institution that houses it, namely Muhammadiyah. From this activity, it is wxpected that students will have the spirit of preaching and invite Amar Ma'ruf Nahi Munkar wherever he is, especially through social media. The approach used in implementing this community service program is an andragogy approach and interactive dialogue based on Forum Group Discussion. As for the method of implementing community service, several meetings are carried out using the method of delivering lectures, discussions, demonstrations, practices, cooperative and inquiry using the provided laptop and mobile phone media. The results of the service program show that there has been an increase in several aspects of the participants' knowledge and skills, including: (1) Increased Knowledge of Digital Literacy, (2) Introduction of Digital Literacy as a Source of Information, (3) Improved Skills in Creating Da'wah Content with Applications on mobile phones , (4) Growing the Spirit of Preaching. From these programs and activities, it is hoped that there will be follow-up from the LKSA Aisyiyah Institute in Batu City to provide a forum for participants in developing and channeling their interests and talents. Which can be used by institutions to maximize and activate the media platform owned by the institution. So that the interests and talents of students are well channeled, and the Institution gets sustainable benefits.